Children after traumatic experiences - Lenart, Angelika (Acta Universitatis Nicolai Copernici. Pedagogika, 2020)
Children who have experienced traumatic events in their lives and grew up in an environment that neglected their needs and in which abuse occurred will feel the long-term and varied impact of these events on their lives. That is why, working with children who have experienced trauma is so important but also difficult. Caregivers and educators should first learn about their history and understand the impact of traumatic events they have experienced before focusing on their behaviour. They ought to build appropriate relationships that will allow to gain confidence and a sense of security. The article presents the phenomenon of trauma and its types, the impact of traumatic experiences on child development and the consequences that follow. It was shown what work with a child should look like after traumatic experiences.